Strategi Komunikasi Baznas Dalam Mensosialisasikan Zakat Sebagai Pengurang Penghasilan Kena Pajak Untuk Pengumpulan Zakat Maal Di Kabupaten Rokan Hulu - M. Zikru Fardan; Noor Efni Salam; Anuar Rasyid (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
This study aims to analyze the communication strategy implemented by the National Zakat Agency of Rokan Hulu Regency in promoting zakat as a tax-deductible contribution, which includes the planning, implementation, and evaluation stages. Furthermore, this study seeks to identify factors that support and hinder the communication process, and measure the impact of these promotional efforts on public understanding, awareness, and participation in distributing zakat through official institutions. This study uses a qualitative approach with descriptive methods, including in-depth interviews, field observations, and official document collection as the main data instruments. Data analysis includes data reduction, systematic presentation of information, and drawing conclusions based on field findings. The research findings indicate that the communication strategy implemented includes identifying the target audience, formulating messages, selecting communicators, and using various media. Communication is carried out through direct and indirect approaches, with face-to-face methods proving more effective in conveying technical understanding to the public. The evaluation shows a positive increase in public understanding, the number of zakat payers, and the total funds collected, although this increase is not evenly distributed across the board. The implemented strategy is considered quite effective but still requires optimization, particularly in communicating technical messages and increasing the frequency of outreach through interactive media.